The effect of tea drugs as a natural adsorbent on the purification of bioetanol from avocado seeds by the process adsorption-distillation - ., Marhaini; ., Mardawita; Wahyuni, Sri (International Journal of Engineering and Technology, 2023)
Starch and cellulose are high molecular weight polysaccharides consisting of carbon, hydrogen and oxygen compounds. One effort that can be made to increase profits from avocado seeds is to transform them into bioethanol. Avocado seeds contain 43.3% amylase, 37.7% amylopectin and 55.07% carbohydrates. The physical properties of waste tea dregs have large surface area and fast adsorption kinetics, which makes waste tea dregs good for use as an environmentally friendly adsorbent. The method is carried out using the Bioethanol Adsorption-Distillation process with activated tea lees. FTIR results of avocado seeds contain C-O, C=O, N=O groups, C=C double bonds, C=C triple bonds, C-H triple bonds and –OH groups, which are a group of carbohydrates containing polysaccharides which can be used as raw material for the manufacture of ethanol and tea dregs contain C-O, C=O, N=O groups, C=C double bonds, C= triple bonds C, C-H triple bonds and –OH groups are carbohydrates, so tea dregs can be used as a raw material to increase bioethanol levels. The results of bioethanol levels using adsorbent and distillation reached high values with a bioethanol refractive index of 1.7575 and an ethanol content of 28% compared to the initial ethanol content of 11.5%.